Japanese colonial language education in Taiwan and assimilation, 1895-1945 - Fewings, Catherine Shu-fen (Yu) (Curtin University, 2004)
This thesis explores the subject of Japanese colonial language education in Taiwan and assimilation between 1895 and 1945. It examines the overall nature of Japanese colonial rule in Taiwan through its colonial policies, followed by a review of the history of Japanese colonial language education in Taiwan, the investigation of the Japanese colonial position on language education and assimilation, the establishment of the implementation of Japanese language education in Taiwan in areas of teaching methodologies and textbook compilation, and the determination of the effects of Japanese language education on assimilation in Taiwan. The thesis further seeks to determine the link between a Taiwanese identity and the Taiwanese who were ruled and educated under Japanese colonial rule. The views of both the elite and common Taiwanese who lived through the colonial era are examined.The aim of this thesis is to test the hypothesis whether Japanese colonial education in Taiwan achieved assimilation among the Taiwanese as claimed by Japanese colonial authorities. Through the official facts and figures provided by Japanese colonial authorities, they seemed to prove a successful case of assimilation among the Taiwanese. However, through close scrutiny of these official facts and figures and reality backed up by the oral accounts of the Taiwanese and conscientious observations by the Japanese, it is found that the claims made by Japanese colonial authorities in the case of assimilation through Japanese language education are highly contestable. By interviewing those who experienced Japanese language education during the colonial period, further insights into the formation of post-colonial Taiwanese identities are gained. This study contributes to studies on Taiwans subsequent socio-linguistic developments in the post-colonial period.